STUDIES OF STRUCTURE AND CHARACTER DETERMINATION FACTOR IN BF3-H2O, HF-H2O, CXHYZ-H2O (X= 4, 5 Y= 4, 5, 6 Z= N, O, P, S) COMPLEXES - CAHYONO (NIM : 10510062) ; Pembimbing Muhamad A. Martoprawiro, Ph.D, EDI
Computational study have performed to determine characteristic and structure of BF3􀀀H2O, HF􀀀H2O, CxHyZ􀀀H2O (X= 4, 5 Y= 4, 5, 6 Z= N, O, P, S) complexes. This calculation perform B3LYP/6-31++G** level theory for geometry optimization. Characteristic such as electronic energy, binding energy, NBO, AIM, frequencies, and solvent effect determined using MP2/6-311++G(2d,2p) level theory. This research result existence of binding orientation of complexes. There are angle deviation qO = 46Ã‚Â° for HF-H2O and BF3-H2O , also qH = 170Ã‚Â° for C4H4S-H2O and qH = 20Ã‚Â° for C5H6S-H2O. Interaction orientation has probability that decrease at increasing energy level. The influencial factor for intermolecular orientation such as donor atom domain, intermolecular binding energy, interaction stability, frequency change, vibrational energy base, and orientation state probability. Besides that, majority of binding energy result comparable with solubility experiment database.